Incremental peritoneal dialysis after unplanned start initiation - Calice-Silva, Viviane; Nerbass, Fabiana Baggio (Frontiers in Nephrology, 2022)
Incremental peritoneal dialysis (PD) is characterized as less than a "standard dose" PD prescription. Compared to standard treatment, it has many potential advantages, including better preservation of residual renal function, lower risk of peritonitis, and decreased care delivery burden while reducing the environmental impact and economic cost. Unplanned PD can be defined when treatment starts up to 14 days after catheter insertion and is recognized as a safe and feasible clinical approach. In this perspective paper, we briefly discuss both strategies and share our experience and clinical routine in managing incremental PD after an unplanned initiation.